Hubungan frekuensi menyusui dan teknik menyusui dengan bendungan asi pada ibu nifas di klinik Alisha Medan - Pemiliana, Putri Diah; Rambe, Kumala Sari; Purwana, Rudi; Novianti, Winda; Harahap, Milna Chairunisa (Journal of Pharmaceutical and Sciences, 2023)
Introduction: Breast engorgement is a damming that occurs due to the obstruction of venous flow or lymphatic ducts caused by the accumulation of breast milk. According to the WHO, in 2021, data revealed that around 17,230,142 mothers faced breastfeeding problems, consisting of sore nipples (56.4%), breast engorgement (36.12%), and mastitis (7.5%). A preliminary survey conducted by researchers in October 2023 identified eight postpartum mothers experiencing breast engorgement. The research objective is to determine the relationship between breastfeeding frequency and breastfeeding technique with breast engorgement in postpartum mothers at Alisha Clinic Medan in 2023. The research method employed is an analytical survey with a cross-sectional approach. The population includes all postpartum mothers at Alisha Clinic Medan, totalling 34 individuals. The sampling technique used is the total population, where all 34 postpartum mothers experiencing breast engorgement are taken as samples, using both primary and secondary data. Results: Based on the research findings, out of 34 respondents, 13 (38.2%) had optimal breastfeeding frequency, while 21 (61.8%) had suboptimal breastfeeding frequency. Additionally, 10 (29.4%) practised correct breastfeeding techniques, while 24 (70.6%) used incorrect techniques. Furthermore, 20 (58.8%) experienced breast engorgement, and 14 (41.2%) did not. The chi-square test results indicate a significant relationship between breastfeeding frequency and breast engorgement (p = 0.012 < α 0.05) and between breastfeeding technique and breast engorgement (p = 0.005 < α 0.05). Conclusion: There is a relationship between breastfeeding frequency and technique with breast engorgement.